Ubiquitination in Plant Meiosis: Recent Advances and High Throughput Methods - Orr, Jamie N.; Waugh, Robbie; Colas, Isabelle (Frontiers in Plant Science, 2021)
Meiosis is a specialised cell division which is essential to sexual reproduction. The success of this highly ordered process involves the timely activation, interaction, movement, and removal of many proteins. Ubiquitination is an extraordinarily diverse post-translational modification with a regulatory role in almost all cellular processes. During meiosis, ubiquitin localises to chromatin and the expression of genes related to ubiquitination appears to be enhanced. This may be due to extensive protein turnover mediated by proteasomal degradation. However, degradation is not the only substrate fate conferred by ubiquitination which may also mediate, for example, the activation of key transcription factors. In plant meiosis, the specific roles of several components of the ubiquitination cascade—particularly SCF complex proteins, the APC/C, and HEI10—have been partially characterised indicating diverse roles in chromosome segregation, recombination, and synapsis. Nonetheless, these components remain comparatively poorly understood to their counterparts in other processes and in other eukaryotes. In this review, we present an overview of our understanding of the role of ubiquitination in plant meiosis, highlighting recent advances, remaining challenges, and high throughput methods which may be used to overcome them.